The synergism of occlusal splints along with therapeutic exercise on individuals with temporomandibular joint disorders – A pilot study - Tanuj Bachani; Fathima Banu Raza; Anand Kumar Vaidyanathan (The Journal of Indian Prosthodontic Society)
Aim: Aberrative occlusal contacts were associated with Temporomandibular disorder (TMD), but whether stabilization splints with therapeutic exercises alleviate the symptoms is unclear. Hence, this study aims to compare the short-term efficacy of occlusal splint therapy and the synergistic effect of therapeutic exercise with occlusal splint therapy for 3 weeks in individuals with TMD. Settings and Design: in-vivo observational pilot study. Materials and Methods: Fourteen participants were grouped based on the type of treatment: Group A, assigned with combination therapy, stabilization splint with therapeutic exercises, and Group B, with only stabilization splint therapy. Surface electromyography (EMG) was taken to evaluate the masseter and temporalis muscle activity at baseline and 2nd week. The patient’s perception of TMD was evaluated using the Fonseca questionnaire at baseline, 48 h, 14th, and 21st days. Statistical analysis: Chi-square statistical analysis was applied to the quantitative data obtained from the Fonseca questionnaire and EMG analysis, with P < 0.05 as significant. Results: Fonseca questionnaire revealed a significant difference between the two groups at 48 h (P < 0.05). EMG outcome showed no significant difference between the groups at baseline and 14th day (P > 0.05). However, the mean muscle activity recorded at the masseter in Group B was increased on 14th day (56.5 ± 3 μV) and an isotonic muscle pattern was observed in Group A. Conclusion: Combination therapy, which included stabilization splint and home care exercises for moderate to severe TMD patients, led to earlier curative changes in the temporomandibular joint and improved functional jaw movements, along with a reduction in pain. An isotonic muscle activity pattern was also observed, confirming the effect of combination therapy.